Meningkatkan Motivasi Belajar Siswa dengan Media Pembelajaran Online Bagi Siswa Kelas VI SDN 15 Luhak Nan Duo - Daryanti Daryanti (Journal on Education, 2022)
This research is based on the low learning motivation of class VI students. The learning conditions during the pandemic period greatly affected the students' desire to learn. While studying at home, students only answer the questions contained in the student worksheets that were collected a few days later. At the time of limited face-to-face’s learning which was carried out in 2021, it was seen that students had very low motivation in learning. Their limited study’s schedule every three days with limited study hours does not make students enjoy learning. The low motivation to attend school, to study independently in accordance with the learning objectives that have been prepared by the teacher cannot be achieved as indicated by low learning outcomes. Based on this problem, The classroom action research was appointed whose purpose was to see the effect of using online media as a tool to increase learning motivation. With the help of online media, subject matter can be studied anytime, anywhere. So that students are expected not to be left behind with lessons and continue to train themselves even though they do not meet the teacher directly. Assisted by online media, the teacher can continue to monitor students in learning. After conducting classroom action research using online media in the form of classroom, WhatsApp, quizzz in overcoming the low learning motivation after two cycles, the results showed significant success.